Platform Inovatif Bagi UMKM Pasca Pandemi Covid-19 UMKM, Industri, Dan Ekonomi Kreatif - Putri, Yustika Kusuma (EXERO : Journal of Research in Business and Economics, 2023)
Covid-19 is an unpredictable event that impacts the economic sector. Micro, Small and Medium Enterprises (MSMEs) play a major role in the Indonesian economy. However, of the 59.9 million MSMEs in Indonesia, the success rate of selling products through digital platforms is only 4%. The obstacles commonly encountered by MSMEs are the lack of knowledge of running an online business as much as and the unpreparedness of workers to use the internet as much. Whereas online media provides a promising market. Therefore, the application "BUSION: Business Solution" which helps MSMEs to find digitization services according to their budget in order to present attractive product visuals and a good social media management system. The method used in this research is the latest literature study so that it can produce accurate and solution outcomes. Then the various features for MSMEs contained in this application are looking for photographers, social media management, and product design. This application also has regional features so that MSMEs can find the best services closest to their current location. In addition to maximizing digitalization and expanding the market, this application can also support the government's 'Go Digital' program to restore the national economy after the co-19 pandemic. The conclusion of this research is that it is proven that the BUSION application is a platform that is feasible to develop in Indonesia in order to revive the national economy after the Covid-19 pandemic.